Association between previous spontaneous abortion and pre‐eclampsia during a subsequent pregnancy. Issue 1 (12th November 2016) - Sepidarkish, Mahdi; Almasi‐Hashiani, Amir; Maroufizadeh, Saman; Vesali, Samira; Pirjani, Reihaneh; Samani, Reza O.
Abstract: Objective: To determine the impact of a history of spontaneous abortion on pre‐eclampsia during a subsequent pregnancy. Methods: A cross‐sectional study enrolled pregnant women admitted to obstetrics and gynecology wards at 103 hospitals in Tehran, Iran for delivery between July 6 and July 21, 2015. Consenting participants were interviewed by midwives; data were collected using a five‐part questionnaire and patients' medical records were retrieved. Patient data were analyzed by multiple logistic regression to identify variables associated with increased odds of pre‐eclampsia. Results: In total, 5170 patients were interviewed and 252 had experienced pre‐eclampsia. The number of previous spontaneous abortions was found to be associated with pre‐eclampsia, and a higher number of previous spontaneous abortions was associated with increased odds of patients having experienced pre‐eclampsia (adjusted odds ratio 1.28, 95% confidence interval 1.03–1.59; P =0.025). Conclusion: A history of spontaneous abortion was associated with increased odds of pre‐eclampsia during a subsequent pregnancy. Abstract : A previous history of spontaneous abortion was associated with greater odds of patients experiencing pre‐eclampsia during a subsequent pregnancy.